ANALISIS INSTALASI LISTRIK MENGGUNAKAN PEMBANGKIT LISTRIK SURYA SKALA RUMAH TANGGA - Retno Aita Diantari; Sofitri Rahayu; Rudina Okvasari (Sutet, 2018)
Indonesia is an archipelago and is located in the tropics. One of the disadvantages of an archipelagic country is that it is difficult to distribute electricity systems centrally, so an easier system needs to be used by utilizing easily available energy sources. Because Indonesia is in the tropics, the source of solar energy is the most appropriate. The purpose of this study is to analysis the electric power generation systems of household as an alternative to meeting electricity needs. From the results of the study, it can be concluded that in the design of a household scale solar power plant it is necessary to calculate solar module capacity, battery capacity, solar charge controller and inverter. Weather and load factors are very influential on the length of a household scale solar power plant operating. The intensity of sunlight received by household scale solar power plant will be high when the sky is clear, and the intensity will decrease if it is in cloudy sky. If the load used is high, the household scale solar power plant will not be able to operate long enough to supply electricity to the load, if the load used is low then the household scale solar power plant can operate relatively longer in supplying electricity to the load.